2014
DOI: 10.5489/cuaj.2312
|View full text |Cite
|
Sign up to set email alerts
|

Men’s mental health: Connection to urologic health

Abstract: Historically,thespecialtyofurologyhasfocusedonsingle-systemdiseases.Inrecentyears,however,therehasbeenincreasingrecognition oftheinterconnectivitybetweenthevarioussystems,suchascardiovasculardisease,metabolicsyndrome,erectiledysfunctionandprostatecancer.Thisconstellationofdisease/syndromeanddysfunction mayplaceurologistsatthecentreofmen'soverallhealthconcerns. Asurologistsconsideringtakingonaleadershiproleinmen'shealth, theyshouldalsoconsidertheirpotentialinhelpingmensufferingfrom thesignificantburdenofamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The consequences of framing individuals as solely responsible for their health are clearly apparent in men's health disparities. Men -the primary arbitrators of these masculine health practices -surpass other genders in their morbidity and mortality rates from a multitude of cancers and diseases, they more often engage in high-risk activities like excessive drinking and speeding, and they suffer biopsychosocial distress when their masculinity comes into question -especially through medical diagnoses of such things as testicular or prostate cancer (Evans et al 2011;Matthew and Elterman 2014;Elder and Griffith 2016). Health and health management under biomedicalization are then seen as articulations and markers of masculinity.…”
Section: »Man I Need Health!«: Toxic Masculinity Men's Health and mentioning
confidence: 99%
“…The consequences of framing individuals as solely responsible for their health are clearly apparent in men's health disparities. Men -the primary arbitrators of these masculine health practices -surpass other genders in their morbidity and mortality rates from a multitude of cancers and diseases, they more often engage in high-risk activities like excessive drinking and speeding, and they suffer biopsychosocial distress when their masculinity comes into question -especially through medical diagnoses of such things as testicular or prostate cancer (Evans et al 2011;Matthew and Elterman 2014;Elder and Griffith 2016). Health and health management under biomedicalization are then seen as articulations and markers of masculinity.…”
Section: »Man I Need Health!«: Toxic Masculinity Men's Health and mentioning
confidence: 99%
“…The consequences of framing individuals as solely responsible for their health are clearly apparent in men's health disparities. Men -the primary arbitrators of these masculine health practices -surpass other genders in their morbidity and mortality rates from a multitude of cancers and diseases, they more often engage in high-risk activities like excessive drinking and speeding, and they suffer biopsychosocial distress when their masculinity comes into question -especially through medical diagnoses of such things as testicular or prostate cancer (Evans et al 2011;Matthew and Elterman 2014;Elder and Griffith 2016). Health and health management under biomedicalization are then seen as articulations and markers of masculinity.…”
Section: »Man I Need Health!«: Toxic Masculinity Men's Health and The Normalization Of Biomedicalization Through Digital Gamesmentioning
confidence: 99%
“…According to this description, it seems clear that functional status domain is well connected with the symptoms and general health perception domain in this model. 66 These strategies should be considered as the first-line approach due to the fact from a recent study in the US Nursing Homes (NHs) reported the high mortality rates and a functional status decline in NH resident after 1-year minor urology surgery including TURP. 64 Coupled with this, urinary incontinence contributes to higher odds of loneliness and is highly associated with mental health problems (ie, depression).…”
Section: Functional Statusmentioning
confidence: 99%
“…65 Urological nurses along with urologist are emphasized to strengthen their role in mental health issues by identifying the current problems, influencing a healthy behaviour change, referring patients when impossible to seek help to appropriate psychological healthcare center. 66 These strategies should be considered as the first-line approach due to the fact from a recent study in the US Nursing Homes (NHs) reported the high mortality rates and a functional status decline in NH resident after 1-year minor urology surgery including TURP. 67 Related to the "social function", a social support approach involving other health professionals is important in preventing social function impairment.…”
Section: Functional Statusmentioning
confidence: 99%